Kingdom-Wide Analysis of Fungal Small Secreted Proteins (SSPs) Reveals their Potential Role in Host Association - Kim, Ki-Tae; Jeon, Jongbum; Choi, Jaeyoung; Cheong, Kyeongchae; Song, Hyeunjeong; Choi, Gobong; Kang, Seogchan; Lee, Yong-Hwan (Frontiers in Plant Science, 2016)
Fungal secretome consists of various functional groups of proteins, many of which participate in nutrient acquisition, self-protection, or manipulation of the environment and neighboring organisms. The least characterized component of the secretome is small secreted proteins (SSPs). Some SSPs have been reported to function as effectors, but most remain to be characterized. The composition of major secretome components, such as carbohydrate-active enzymes, proteases, lipases, and oxidoreductases, appear to reflect the lifestyle and ecological niche of individual species. We hypothesize that many SSPs participate in manipulating plants as effectors. Obligate biotrophs likely encode more and diverse effector-like SSPs to suppress host defense compared to necrotrophs, which generally use cell wall degrading enzymes and phytotoxins to kill hosts. Because different secretome prediction workflows have been used in different studies, available secretome data are difficult to integrate for comprehensive comparative studies to test this hypothesis. In this study, SSPs encoded by 136 fungal species were identified from data archived in Fungal Secretome Database via a refined secretome workflow. Subsequently, compositions of SSPs and other secretome components were compared in light of taxa and lifestyles. Those species that are intimately associated with host cells, such as biotrophs and symbionts, usually have higher proportion of species-specific SSPs (SSSPs) than hemibiotrophs and necrotrophs, but the latter groups displayed higher proportions of secreted enzymes. Results from our study established a foundation for functional studies on SSPs and will also help understand genomic changes potentially underpinning different fungal lifestyles.